ANALISIS ALIRAN INFORMASI KOMUNIKASI INTERNAL DALAM IMPLEMENTASI MOBILE WORKING PADA PERUSAHAAN MEDIA PENYEDIA KONTEN INTERNAL MAGAZINE (Studi Kasus di PT Tanair Media Seruni) - Budi Suswanto (MediaKom : Jurnal Ilmiah Komunikasi, 2016)
Changes in internal communications technology company influence the development of communication technology. Internal communication through physical meetings members initially turned into mobile technology. The study aims to analyze the flow of internal communication of information on the implementation of mobile working in PT Tanair Media chrysanthemum, coordination and management tasks with a mobile system working. Data were collected through direct observation in the field, in-depth interviews to five key informants and documentation. The study was conducted by using a qualitative approach with constructivism. The theory is Communicative Constitution of Organizations and Weick. Discussion of the results obtained conclusions: (1) Changes in the system of internal communication technology-based organizations keep up with technology, (2) The use of social media technologies and application-oriented Media Vista duties and functions, (3) Coordination management tasks with mobile working systems tailored to the plan, organize, action and control.